2017
DOI: 10.21817/ijet/2017/v9i3/1709030186
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Surface Condenser in 525MW Thermal Power Plant

Abstract: Abstract-This paper presents off design performance evaluation and calculation methodology of a surface type condenser. Best condenser pressure which can be achieved in actual off design conditions has been evaluated by real time parameters. Condenser performance study has been carried out for cooling water flow, cooling water inlet temperature, and for air ingress/dirty tubes. This method can be proved useful in the case where no curve regarding variation of condenser back pressure verses cooling water inlet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…( 6) Fixed total surface area of condenser tubes and material properties. (7) There is no pressure drop across the condenser. (8) Constant condenser heat transfer area and heat load.…”
Section: Model Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…( 6) Fixed total surface area of condenser tubes and material properties. (7) There is no pressure drop across the condenser. (8) Constant condenser heat transfer area and heat load.…”
Section: Model Assumptionsmentioning
confidence: 99%
“…Reference [6] investigated, by a thermodynamic model, the impact of flow rate, temperature and velocity of the cooling water on the heat transfer and condenser effectiveness, for a coal fired plant, and found that 1 °C increase in the inlet temperature of cooling water leads to deviation of the condenser pressure by 0.59 kPa, which reduces the cycle heat transfer rate by 0.36% and the unit generation by 33 MW. An experimental work on the performance of a steam condenser in a 600 MW thermal PP depicted that the plant efficiency increased from 38.83% to 39.45% by reducing the condenser pressure to 65.21 bar [7] . A research on the effect of the condenser [8] .…”
Section: Introductionmentioning
confidence: 99%
“…[ 3,13–15 ] The efficiency of atmospheric water collection (as well as the efficiency of processes of industrial relevance, such as heat transfer in cooling towers) depends on the ability of a surface to first nucleate water droplets at a high rate, and shed those droplets at low volumes, so they can be collected. [ 16–19 ]…”
Section: Introductionmentioning
confidence: 99%
“…[3,[13][14][15] The efficiency of atmospheric water collection (as well as the efficiency of processes of industrial relevance, such as heat transfer in cooling towers) depends on the ability of a surface to first nucleate water droplets at a high rate, and shed those droplets at low volumes, so they can be collected. [16][17][18][19] Classical nucleation theory teaches that the free energy barrier for nucleation ΔG is lower for ideal planar surfaces that are highly wettable by water (low water contact angle), and can be estimated by the following equation [20]…”
mentioning
confidence: 99%
“…Steam condenser efficiency, amount of heat transfer, vacuum pressure inside the chamber, and the performance and energy generation of the LP part of the steam turbine are assessed. Masiwal et al [11] presented off-design performance evaluation and calculation methodology of a surface type condenser. Condenser performance study has been carried out for cooling water flow, cooling water inlet temperature, and air ingress/dirty tubes.…”
Section: Introductionmentioning
confidence: 99%